Integrative analysis of Text-to-Image AI systems in architectural design education: pedagogical innovations and creative design implications - Montenegro, Nuno (Journal of Architecture and Urbanism, 2024)
This study explores the potential of Text-to-Image (T2I) AI systems in architectural design education, particularly during the conceptual design phase. Through a structured two-stage workshop, architecture students used T2I AI to conceptualize a public building project, focusing on the bird’s eye and interior perspectives. These AI-assisted designs were subsequently refined to align with specific site conditions and programmatic requirements. The study reveals T2I AI’s ability to expand creative possibilities in architectural design while highlighting its limitations and biases. The findings emphasize the necessity for a critical and informed approach when integrating AI into architectural education and practice, addressing ethical considerations. Future research directions are proposed to optimize T2I AI applications in architectural design, address inherent biases in AI systems, and enhance the discourse on AI’s role in shaping the future of architectural practices.